If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying j = 5a + -1(5a + -5) Reorder the terms: j = 5a + -1(-5 + 5a) j = 5a + (-5 * -1 + 5a * -1) j = 5a + (5 + -5a) Reorder the terms: j = 5 + 5a + -5a Combine like terms: 5a + -5a = 0 j = 5 + 0 j = 5 Solving j = 5 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Simplifying j = 5
| (n-6)(n-1)(n-2)(n-3)(n-4)(n-5)=0 | | 5=3(3-2x)+4(6-2x) | | (2+n)(n-1)(n-2)(n-3)(n-4)(n-5)=0 | | 6a^2x^2-abx-5b^2=0 | | 3x-12-1(x+4)=0 | | 10y-3=7y+9 | | 14+3n=20 | | 2(y-2)+5(2-y)=-3y(2y+2) | | 4*2x+1+5*2x+1=200*x | | x^4=2x^2+63 | | x^2-10x=-1025 | | x(x+4)(2x+5)=0 | | 7x+20=72 | | 4(2x-5)=5+4 | | a=5(x+8) | | xx+2x+7=7 | | A-40=5x | | 5X*3+3X=13 | | a=5x+40 | | 1.7+5(2.1x+0.4)=2 | | 6x+4y=95 | | 7x+20=56 | | 8=x+8.4-1.2x | | 8y+13= | | 8(y-3)-3=56 | | 28y+5=49 | | 28y+5=27 | | 2x+167=11x-13 | | 7m-11=59 | | 9h+6=87 | | 7m+3=59 | | sin(2x+5)=sin(x-1) |